Question
upstudy study bank question image url

Find the solution to the system by the substitution method. Check your answers. \( \begin{array}{r}7 x+4 y=86 \\ x+2 y=-2\end{array} \) Select the correct choice below and, if necessary, fill in the answer box to complete your choice.

Ask by Cruz Reid. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solution is \( x = 18 \) and \( y = -10 \).

Solution

Solve the system of equations \( 7x+4y=86;x+2y=-2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}7x+4y=86\\x+2y=-2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}7x+4y=86\\x=-2-2y\end{array}\right.\) - step2: Substitute the value of \(x:\) \(7\left(-2-2y\right)+4y=86\) - step3: Simplify: \(-14-10y=86\) - step4: Move the constant to the right side: \(-10y=86+14\) - step5: Add the numbers: \(-10y=100\) - step6: Change the signs: \(10y=-100\) - step7: Divide both sides: \(\frac{10y}{10}=\frac{-100}{10}\) - step8: Divide the numbers: \(y=-10\) - step9: Substitute the value of \(y:\) \(x=-2-2\left(-10\right)\) - step10: Simplify: \(x=18\) - step11: Calculate: \(\left\{ \begin{array}{l}x=18\\y=-10\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=18\\y=-10\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(18,-10\right)\) The solution to the system of equations by the substitution method is \( (x,y) = (18,-10) \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To solve the system by substitution, we first solve one equation for one variable. Let's take the second equation \( x + 2y = -2 \) and solve for \( x \): \[ x = -2 - 2y \] Now we can substitute this expression for \( x \) into the first equation \( 7x + 4y = 86 \): \[ 7(-2 - 2y) + 4y = 86 \] Distributing: \[ -14 - 14y + 4y = 86 \] \[ -14 - 10y = 86 \] Next, isolate \( y \): \[ -10y = 86 + 14 \] \[ -10y = 100 \] \[ y = -10 \] Now substitute \( y = -10 \) back into the expression we found for \( x \): \[ x = -2 - 2(-10) \] \[ x = -2 + 20 \] \[ x = 18 \] So, the solution to the system is \( (18, -10) \). Now, let's check the solution by substituting \( x = 18 \) and \( y = -10 \) back into both original equations: 1. For the first equation: \[ 7(18) + 4(-10) = 126 - 40 = 86 \] (checked) 2. For the second equation: \[ 18 + 2(-10) = 18 - 20 = -2 \] (checked) Both equations are satisfied, so the solution \( (18, -10) \) is correct!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy